Pengaruh Permainan Bowling Huruf terhadap Kemampuan Mengenal Kata pada Anak Usia Dini - Dessi Andriani; Nadirahsyahla, Shinta; Taty Fauzi (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine the effect of the letter bowling game on the ability to recognize words in group B children at the Fathiyyah Integrated Islamic PAUD. This type of research is a Pre-Experimental type of experimental research by providing treatment in the form of a letter bowling game method to students, then comparing the ability to recognize words in children before and after being given a letter bowling game. The sample used in this study was the total number of B grade children in the Fathiyyah Integrated Islamic PAUD. The method used in collecting research data is through a checklist observation sheet. The method in analyzing research data is the t-test. The results of the study based on the t-test calculation found that the value of fcount < ftable or 1.26 < 2.33 means Ho is rejected and Ha is accepted. It can be concluded that there is an effect of the letter bowling game on the ability to recognize words in group B children at the Fathiyyah Integrated Islamic PAUD. It can be suggested that the letter bowling game should be used in word recognition lessons for other classes.